The response of benthic foraminifer, ostracod and mollusc assemblages to environmental conditions: a case study from the Camalti Saltpan (Izmir-Western Turkey) - MERIC, E.; AVSAR, N.; NAZIK, A.; BARUT, F.; BERGIN, F.; BALKIS, N.; ONCEL, M.S.; KAPAN-YESILYURT, S. (Mediterranean Marine Science, 2010)
The subject of this report is benthic foraminifer populations preserved in the saltpan of Camalti in the Province of Izmir. High salinity in certain habitats of Ammonia tepida Cushman may be the primary cause of the high rate of twins and triplets as well as other morphological abnormalities recorded within this species (50 % as compared to an anomaly rate of 1 % in normal marine waters). Thicker cyst membrane developing in extremely saline environments may encourage twins and other morphological deformities by denying free movement of the offspring. Ecological factors such as heavy metal contamination of ambient waters as well as contamination by other wastes are also not ruled out as leading to such developmental anomalies. Of the 27 collected samples, Number 5 (that is closest to the sea) includes the typical marine foraminifers. Nonion depressulum (Walker & Jacob), Ammonia tepida Cushman and Porosononion subgronosum(Egger) are the dominant species in other samples. A total of 63 abnormal individuals (8 triplets, 24 twins, and 31 morphological anomalies) was found within seven of the 27 samples collected. Ten samples contained freshwater ostracods: Darwinula stevensoni(Brady and Robertson), Leptocythere lacertosa Hirschmann, Cyprideis torasa (Jones), Cyprideis (C.) anatolica Bassiouni, and Loxochoncha elliptica Brady. Among these samples (some of which contained only a few species of ostracods - and those limited in number of offspring), one had an unusually high ratio of healthy foraminifers vs those with anomalies. Worthy of note in another sample was a high abundance of molluscs. Among pelecypods, were found Ostrea edulis Linné, Lucinella divaricata (Linné), Pseudocama gryphina Lamarck,Cerastoderma edule (Linné), and Scrobicularia plana da Costa; and among gastropods were identified Hydrobi (Hydrobia) acuta(Draparnaud), Rissoa labiosa (Montagu), R. parva (da Costa), R. violacea Desmarest, Pirenella conica (Blainville), Bittium desayesi(Cerulli and Irelli), B. lacteum Philippi and B. reticulatum Philippi.